Discursive Constructions of Corporate Identities by Chinese Banks on Sina Weibo : An Integrated Sociolinguistics Approach - Feng, Wei (Springer Singapore : Imprint: Springer, 2017)
This book addresses the discursive construction of corporate identities in social media on the part of Chinese corporations, particularly highlighting how followers of corporate social media co-create corporate identities during firm-follower interactions. Toward this end, it pursues an integrated sociolinguistics approach combining e.g. thematic analysis, interactional analysis and in-depth interviews. Readers will also find extensive information on the brand-new dialogic framework of corporate identity formation. The book offers an insightful and revealing guide for both practitioners/trainers and teachers in corporate communication who are faced with the challenges of managing public relations and corporate images in the age of social media. It can also serve as a valuable case study for those readers who are fascinated by the Chinese economy and discourse analysis of the Chinese language.
Keywords: Linguistics.; Communication.; Sociolinguistics.; Discourse analysis.; elektronické knihy; electronic books